Emergency department initiated resuscitative endovascular balloon occlusion of the aorta (REBOA) for out‐of‐hospital cardiac arrest is feasible and associated with improvements in end‐tidal carbon dioxide. Issue 5 (10th September 2022) - Daley, James; Buckley, Ryan; Kisken, Kathryn Cannon; Barber, Douglas; Ayyagari, Raj; Wira, Charles; Aydin, Ani; Latich, Igor; Lozada, Juan Carlos Perez; Joseph, Daniel; Marino, Angelo; Mojibian, Hamid; et al.
Abstract: Objectives: Out‐of‐hospital cardiac arrest (OHCA) claims the lives of approximately 350, 000 people in the United States each year. Resuscitative endovascular balloon occlusion of the aorta (REBOA) when used as an adjunct to advanced cardiac life support may improve cardio‐cerebral perfusion. Our primary research objective was to determine the feasibility of emergency department (ED)‐initiated REBOA for OHCA patients in an academic urban ED. Methods: This was a single‐center, single‐arm, early feasibility trial that used REBOA as an adjunct to advanced cardiac life support (ACLS) in OHCA. Subjects under 80 years with witnessed OHCA and who received cardiopulmonary rescuitation (CPR) within 6 minutes were eligible. Results: Five patients were enrolled between February 2020 and April 2021. The procedure was successful in all patients and 4 of 5 (80%) patients had transient return of spontaneous circulation (ROSC) after aortic occlusion. Unfortunately, all patients re‐arrested soon after intra‐aortic balloon deflation and none survived to hospital admission. At 30 seconds post‐aortic occlusion, investigators noted a statistically significant increase in end tidal carbon dioxide of 26% (95% confidence interval, 10%, 44%). Conclusion: Initiating REBOA for OHCA patients in an academic urban ED setting is feasible. Aortic occlusion during chest compressions is temporally associated with improvements in end tidal carbon dioxide 30 seconds after aortic occlusion. Four of 5 patients achieved ROSC after aortic occlusion; however, deflation of the intra‐aortic balloon quickly led to re‐arrest and death in all patients. Future research should focus on the utilization of partial‐REBOA to prevent re‐arrest after ROSC, as well as the optimal way to incorporate this technique with other endovascular reperfusion strategies.